2021
DOI: 10.1371/journal.pone.0245126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of blaSHV, blaTEM, and blaCTX-M in extended-spectrum β-lactamase producing Enterobacteriaceae recovered from fecal specimens of animals

Abstract: Colonization of extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae as animal gut microbiota is a substantial global threat. This study aimed to determine the molecular characterization of blaSHV, blaTEM, and blaCTX-M variants in animals, as well as to evaluate the antimicrobial resistance conferred by these genes. We prospectively analyzed 1273 fecal specimens of farm and domestic animals for the isolation of enterobacteria that had the ESBL phenotype by using biochemical methods. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
5
34
6
2
Order By: Relevance
“…Genes encoding ESBL were amplified from all phenotypically characterized ESBL producers. Previously reported primers for bla SHV , bla TEM , and bla CTX-M were used, and the PCR conditions were optimized [18]. PCR conditions were followed as: initial denaturation at 95 • C for 3 min; 30 cycles of 15 s at 95 • C, 56 • C for 35 s and 72 • C for 1 min; finally, a 7 min extension step at 72 • C. The amplified products were visualized by agarose gel electrophoresis, and product sizes were determined using a DNA ladder (100 bp).…”
Section: Molecular Characterization Of Mcr Genesmentioning
confidence: 99%
“…Genes encoding ESBL were amplified from all phenotypically characterized ESBL producers. Previously reported primers for bla SHV , bla TEM , and bla CTX-M were used, and the PCR conditions were optimized [18]. PCR conditions were followed as: initial denaturation at 95 • C for 3 min; 30 cycles of 15 s at 95 • C, 56 • C for 35 s and 72 • C for 1 min; finally, a 7 min extension step at 72 • C. The amplified products were visualized by agarose gel electrophoresis, and product sizes were determined using a DNA ladder (100 bp).…”
Section: Molecular Characterization Of Mcr Genesmentioning
confidence: 99%
“…Furthermore, the close contact between animals and humans facilitates cross-transmission, especially members of the Enterobacterales which are closely related normal intestinal flora that rarely cause disease in normal hosts. However, they can cause serious disease in immunocompromised patients due to other diseases [ 4 ], and have the ability to acquire and disseminate several unique resistance mechanisms [ 25 , 26 ]. The emergence and spread of ESBL- and Amp-producing Enterobacteriaceae from animals has become an important community concern worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been growing reports that elucidate and support the potential link between the emergence of AMR in humans and AMR in livestock populations [ 2 , 3 ]. Gram-negative bacteria, especially Enterobacteriacea, are of grave concern as their emergence and transmission, particularly extended-spectrum beta-lactamase (ESBL) and AmpC-producers from animals, have become a critical worldwide community concern [ 4 ]. The uncontrolled use of antibiotics in humans and animals, coupled with the use of human antibiotics in veterinary medicine has resulted in increasing the rates of AMR, especially in developing countries including Egypt [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, similar studies have revealed that the prevalence rates of ESBL-producing E. coli from companion animals in China and Japan were 24.5% and 28%, respectively [ 11 , 12 ]. In a study conducted in Pakistan, 15.3% of Enterobacteriaceae in companion animals were noted to be ESBL producing [ 13 ]. A high prevalence of ESBL-producing E. coli in Asian countries warrants concern.…”
Section: Discussionmentioning
confidence: 99%